Social Attitudes and Values of Young People in the Context of Multicultural Education - Cabanova, Vlasta (Communications - Scientific letters of the University of Zilina, 2014)
As a result of globalisation, more situations where pupils meet other cultures arise. Fears of unknown and also other factors contribute to the refusal of being alternate, which is expressed, in terms of human behaviour, in the form of prejudices. Educational effect of pedagogues should help eliminate these barriers among children.